Clear cell carcinoma palisading in a focus of endometriosis on the uterine serosa - A case report and review of the literature - Vishal Bahall; Lance De Barry; Colin Jaggernauth (Elsevier, 2022)
Background: Clear cell carcinoma arising from the malignant transformation of endometriosis is a rare but aggressive cancer often diagnosed in perimenopausal women. Malignant transformation constitutes a rare complication of endometriosis, with only a few cases reported in the medical literature. Clear cell carcinoma and endometrioid carcinoma are the two most common histological subtypes associated with malignant endometriosis. Case Presentation: A 61-year-old Afro-Trinidadian woman underwent a total abdominal hysterectomy and bilateral salpingo-oophorectomy for a degenerated uterine leiomyoma. Histopathology demonstrated an isolated finding of clear cell carcinoma occurring within an endometriotic cyst on the uterine serosa. Subsequent surgical staging demonstrated early-stage disease associated with a high-risk histological subtype and the patient was referred for adjuvant chemoradiotherapy. Conclusion: This case highlights the clinical manifestations and treatment modalities employed for an early-stage high-risk subtype of endometriosis-associated cancer. In light of the few publications on this clinical entity, we hope to raise awareness of this unique complication of endometriosis and contribute evidence to the development of standardized treatment protocols.